Global Synergy, Local Impact : Optimizing Information Retrieval In Lampung Community Libraries Through Information Literacy Training Program By Lampung University And Charles Sturt University - Andi Windah; Ida Nurhaida; Purwanto Putra; Arnila Purnamayanti; Eri Maryani (International Journal Of Community Service, 2025)
International cooperation in community service is becoming increasingly crucial in the era of globalization. The D3 Library Study Program, FISIP Unila, in collaboration with the School of Information and Communication Studies-Charles Sturt University, carried out Community Service in International Cooperation (PKMKI) with a focus on improving information literacy for community library managers in Lampung Province. In an era of abundant information, the ability to search for accurate and relevant information is becoming increasingly important. However, many individuals have difficulty navigating the vast ocean of information. This service aims to overcome this problem by providing training on advanced information search techniques, especially through Google Advanced Search Operators. The methods used in this service include literature studies, field observations, interviews, and Focus Group Discussions (FGD) with community library managers. The results of this service are expected to improve the ability of library managers to provide better information services to the community. The outputs produced include a final service report, financial report, video documentation, and information literacy training modules.